Development And Validation of An Educational Website On Teaching Materials To Enhance Preschool Teachers' Teaching Skills, in Digital Era - Abdi Mohamed, Ahmed; Sunardi; Nur Arifah Drajati (IAIN Madura, 2025)
Preschool teachers in Mogadishu, Somalia, face significant challenges due to limited access to quality and relevant teaching materials, hindering effective instruction and early childhood development. This study addresses the issue by developing an educational website aimed at enhancing teaching skills. Using the Research and Development (R&D) method with the ADDIE model, the study focused on the design and development phases. Validation data were obtained from three educational technology experts and three material experts via validation forms assessing components such as e-books, assessment tools, and teaching tips. Teaching materials were evaluated based on quality, usability, functionality, and educational content. Material experts rated the website at 4.3, classifying it as “very valid” and ready for use without revision. Media experts rated the site 4.1, suggesting minor grammatical corrections and more engaging animations, which were implemented. Stage 2 validation confirmed the website’s readiness for classroom use. The study presents a validated, practical educational website tailored to the specific needs of preschool teachers in Mogadishu, serving as a platform to bridge the gap in teaching resources and support early childhood education effectively.